COMPETENCE "QUALITY" PRACTICES AMONG SPECIAL NEEDS PRESCHOOL TEACHER : PARENTS AND GUARDIANS PERSPECTIVES (Proceedings of International Conference on Special Education, 2017)
The study aims to find special needs preschool teachers practice competencies through the assessment of the quality management practices of special needs preschool teachers from the perspective of parents. The study involved a special needs preschool teacher who follows the Teaching Graduate Program (TGP), organized by the Institute of Teacher Tranning Collage, (ITTC-MOE), especially in the IPG Kampus Bahasa Melayu Kuala Lumpur. Six constructs evaluation assessed the quality of management practices is of the quality aspects of space management, quality management routine, quality of curriculum management, quality management, organization behavior management quality, and the quality of relationship management. This survey includes the perspectives of parents or guardians of students. A questionnaire containing 30 items provided to the parent or guardian. Data were analyzed in the form of descriptive statistics, involving the analysis in terms of frequency, average score and percentage. The study found the quality of management practices in pre-school teachers as a whole is at a moderate level and satisfy the response of parents and guardians. Therefore, the overall quality of the six constructs assessed practice shows that the achievement of 'good'. The views of parents on the strength of quality practices is a special needs preschool teacher in terms of curriculum, student development and teaching-learning activities, as well as the interaction of teachers and students. Accordingly, the requirements of kindergarten teachers to continue to be given exposure and training to educational information of the 21st century as well as the educational goals of developing life human is necessary, in order to meet the aspirations of the country's education and realizing national education policy, as well as to a concern for the challenges of global education in 21st century.